Effect of Boiler Feed Water Quality in Textile and Other Industries - Babiker, Musa Eltayib; Ahmed, Mutasim Abdalla (Gezira Journal of Engineering and Applied Sciences; مجلد 12 عدد 1 (2017), 2017)
Chemical processing of textile is one of the major streams in textile industry in which many activities are included such as, preparation, dyeing and finishing due to its importance for value addition. This study aims to assess the constituents of boiler feed water for different industries. The study was limited to, Blue Nile Textile Company, Gematex Textile Company, Kenana Sugar Company and Khartoum Refinery Company. Boiler feed water samples from each industry were collected using standard sampling techniques at different intervals of times, before and after treatment. Various analytical and instrumental test methods were carried out, using UV- visible and atomic absorption spectrophotometers, flame photometers, turbidity and pH meters. Results of pH, EC, TDS, hardness, anions and cations were determined and compared to the standard ASME guidelines. It is found that all water samples of the four industries constitute various anions and cations with varying degrees. Gematex company showed the highest values of total hardness, calcium ions, carbonates and bicarbonates ions comparative to the other industries, and mostly exceeding the ASME Guidelines. K.S.C. and K.R.C. showed lower levels of impurities because, their boiler feed water was relatively better treated and conditioned, although some results of their tested water samples exceeded the ASME Guidelines. High levels of total hardness, in the boiler water may cause problems concerning boiler performance. pH levels of all companies were found to be below the specified standard guidelines, therefore dealkalization should  be carried out to avoid corrosion. The four companies need proper treatments to reduce the levels of anions and cations within the recommended ASME Guidelines. A reliable water treatment unit is highly recommended for every industry adopting boilers for steam generation. A reverse osmosis system is to be added to the line of treatment as it removes physically anions and cations. Micro processing indicators that can digitally display chemical measurements of some properties of the treated water in – line with the treatment process is also recommended. Application of a genuine, stringent legal testing, training and certification systems may be imposed by the ministry of industry and inspect periodically the conditions of the boilers of the industry in the country.